Journalism and History - Coseriu, Eugenio (Acta Universitatis Danubius. Communicatio, 2023)
In this translated article (which, initially, was a conference delivered in Barcelona in 1991), Eugenio Coseriu dealt with the relation between journalism and history, presenting, most of all, his conception about journalism and its mission in the modern world. Thus, the Romanian scholar added new ideas to his previous study regarding the relation between journalism and literature. During his stay in Barcelona, as an invited speaker, Coseriu had the chance to read the first doctoral thesis (in the world) devoted to journalism, a dissertation defended in 1690, at the University of Leipzig, by Tobias Peucer and published in the same year. Consequently, Coseriu also commented extensively on Peucer’s text and made some very interesting remarks.